Drought in Northeast Brazil: A review of agricultural and policy adaptation options for food security. Issue 1 (21st September 2021) - Marengo, Jose A.; Galdos, Marcelo V.; Challinor, Andrew; Cunha, Ana Paula; Marin, Fabio R.; Vianna, Murilo dos Santos; Alvala, Regina C. S.; Alves, Lincoln M.; Moraes, Osvaldo L.; Bender, Fabiani
Abstract: The semiarid lands of Northeast Brazil represent one of the most densely populated regions of the country. Rainfall variability together with land degradation and large‐scale poverty in rural areas makes this region vulnerable to droughts. Most of the agriculture in this region is rainfed and deficient rainfall leads to severe drought impacts. In this review, we examine different short‐ and long‐term strategies directed to cope with possible impacts of droughts proposed by the government, farmers, civil society, and the private sector. These are approaches to adaptation to drought in the Northeast of Brazil, and among them, we have agricultural management and soil conservation and better management of water resources. Other actions include seasonal climate forecasts and funds transfer and credits to affected small‐scale farmers. Although some of these actions are for the short term and may help to survive the drought situation, they may be only postdisaster mitigation options that do not improve adaptive capacity. They favor maladaptation and create dependency of farmers to government actions. Some experiences such as AdaptaSertão show potential benefits for small‐scale farmers. We identify key challenges for moving toward a more holistic risk management approach and highlight the need to integrate actions and tools for adaptation, combining technology‐based solutions with in‐depth knowledge of local and regional social, economic, and cultural aspects, among them seasonal climate forecasts and drought impacts studies, among some other proactive predisaster ways, rather than reactive postdisaster actions. Adaptation strategies must increase long‐term resilience of food production in the Brazilian Northeast, going beyond an individual drought event. Abstract : The semiarid lands of Northeast Brazil NEB represent one of the most densely populated regions of the country. Rainfall variability together with land degradation and large‐scale poverty in rural areas make this region vulnerable to droughts in the present. Approaches to adaptation to drought in the NEB vary from agricultural practices and credits to farmers to infrastructure and climate forecasts. Adaptation strategies must increase long‐term resilience of food production in the Brazilian Northeast, going beyond an individual drought event.